Methods of assessing pain in newborns and infants - Rozalska-Walaszek, Ilona; Aftyka, Aftyka (Nursing in the 21st Century, 2014)
METHODS OF ASSESSING PAIN IN NEWBORNS AND INFANTS Postoperative pain is an unpleasant experience, which can reduce patient’s quality of life, prolong recovery process, and increase the duration of hospital stay and costs of hospitalization. To assess pain properly, special tools should be used. The biggest challenge for healthcare-professionals is to assess pain in children younger than 3 years old, who can’t speak or aren’t able to assess pain intensity. Therefore, the staff who takes care of child, should know the basic tools for monitoring pain. The aim of the study is to discuss several scales especially adapted for this age group and the presentation of the most commonly used analgesic drugs.